Process parameters optimization in CNC turning of aluminum 7075 alloy using TOPSIS method coupled with Taguchi philosophy. (2022) - Kanaujia, Neetu; Rahul,; Behera, Jitendra Kumar; Kumar Mohapatra, Sambit; Behera, Asit; Jha, Pushkar; Kishore Joshi, Kamal; Chandra Routara, Bharat
Abstract: Aluminum 7075 is a very useful metal as it is used extensively in various fields of engineering like aerospace, constructions, electronics industry etc. As modern industry demand is very high accuracy of products in shorter period of time; so CNC machines are perfect solution for it. CNMG120408 uncoated carbide inserts used for machining of aluminum 7075. So in this research work, we studied the outcome of different parameters (i.e. cutting velocity (Vc), feed rate (Vf ), depth of cut (Dc ) and coolant pressure (Pc )) on the responses like material removal rate (MRR), surface roughness (Ra ) and tool tip temperature (Tavg ). Our primary objective is to find out such a parametric settings in that MRR will be maximum and Ra and Tavg is will be minimum. Here we used L16 orthogonal array and the results were optimized by TOPSIS method integrated with Taguchi philosophy.